Factors affecting research environment at Syrian business faculties: a student-perceived model - Khalifa, Bayan; Abdulraouf, Riad; Mouselli, Sulaiman (Business, Management and Economics Engineering, 2016)
This study aims at investigating the factors that affect the research environment of business postgraduate students, particularly master students, from the perspective of these students. From the same perspective, it also aims at assessing these factors together with the quality of research environment. A questionnaire survey method was employed. The questionnaire was developed by academics from five business faculties based on relevant studies and was distributed to graduate students enrolled in all of the research business programs at the Faculty of Economics, Damascus University, ending up with 88 valid responses. To explore the factors that may affect research environment, exploratory factor analysis was employed. In addition, multiple regression analysis and t-test were applied to respond to the study purposes. Facilities and industry linkage come to be significant factors in the research environment. However, the results show insignificant impact for each of the research courses, networking, and research skills in the overall research environment. Variations in regard to the availability of these factors were identified with low level of availability for the facilities and industry linkage. The study is one of a kind that investigates factors affecting research environment of postgraduate students and particularly master students. Further and to the best of our knowledge, it is the first study that examines such factors in war conditions, which enables us to understand what students perceive as critical factors influencing their research performance in these conditions. Recommendations to policy makers are presented to develop strategies that respond to students’ concerns for a better research environment.